The Impact of ZISWAF Funds, ROE, and MSR on Mudharabah Income in Indonesian Islamic Banking (Period: 2018–2023) - Fahmi, Fahmi Ilham Fadjar; Wahyu Setya Budianto, Eka (Indonesian Journal of Islamic Economic Law, 2025)
This research aims to determine and test the effect of receiving ZISWAF, ROE and MSR funds on Mudharabah income with Firm size as a Moderating Variable. The samples used in this research are companies in the financial sector whose financial data is registered with the Central Statistics Agency. 2018 – 2023. The sampling technique used was purposive sampling, with a total sample of 5 banks in 5 years. The data analysis technique used is Panel Data Regression Analysis and Moderated Regression Analysis (MRA) with the Eviews 12 application. The research results show that ZISWAF funds have a significant positive effect on Mudharabah income for the 2018-2023 period. Return on Equity (ROE) has a significant positive effect on Mudharabah Income for the 2018-2023 period. Legal Reserve Requirement (LLR) has a positive effect on Mudharabah Income. Firm Size is able to moderate the influence of ZISWAF, ROE, LLR Funds on Mudharabah Income for the 2018-2023 period. In future research, it is hoped that other variables will be used as moderating variables, such as dividend policy, etc. and also use samples from other sectors so that the research results can also represent other sectors.